A Case of Unresectable Papillary Thyroid Carcinoma Treated with Lenvatinib as Neoadjuvant Chemotherapy. (11th May 2020) - Iwasaki, Hiroyuki; Toda, Soji; Ito, Hiroyuki; Nemoto, Daiji; Murayama, Daisuke; Okubo, Yoichiro; Hayashi, Hiroyuki; Yokose, Tomoyuki
Abstract : A 75-year-old woman visited a nearby clinic with complaints of right clavicle discomfort, and she underwent diagnostic thoracoscopic lung biopsy, being diagnosed with lung metastasis and a right-upper mediastinal mass. The superior mediastinum mass was extrapulmonary and covered by the pleura, and it was not biopsied. Papillary thyroid carcinoma was diagnosed following biopsy of the lung metastasis. Only a small tumor, with a maximum diameter of 70 mm from the right neck to the superior mediastinum, in the thyroid gland invades the internal jugular vein and subclavian vein, forming a tumor embolus in the right brachiocephalic vein and reaching the vicinity of the superior vena cava. For life-saving purposes, we obtained approval from the Cancer Board of Kanagawa Cancer Center and used lenvatinib according to unresectable undifferentiated cancer IRB approval number 28–41. The tumor had shrunk after 4 months, and surgery was performed. The postoperative course has been good, and the patient is being followed up. The patient is alive three months after surgery, and lung metastases have disappeared on CT images. This case is reported as a successful case of neoadjuvant chemotherapy and interval debulking surgery.